Lion lessons 7 easy steps - Agee, Jon 1960- (Scallywag Press Ltd, 2020)
'It's not easy getting your Lion Diploma.' So Jon Agee's little narrator begins his hilarious description of the crash course he took on becoming an honorary lion. At first he doesn't score high, but when it comes to rescuing an endangered neighbourhood cat, the lion in him is unleashed!
Keywords: Bullying / Pictorial works / Juvenile fiction; Bullying; Children's stories / Pictorial works; Picture books; Bilderbuch